Comparison of the Effectiveness of Training Based on Transactional Analysis (TA) and Pilates Exercises on Psychic Restlessness and General Health of Infertile Women - Susan Belir; Kourosh Goodarzi; Mehdi Roozbahani; Mohammad Ismail Ebrahimi; Keivan Kakabraee (Hamadan University of Medical Sciences, 2022)
Background and Objective: Infertility, as one of the most common diseases of women, is a complex life crisis that is associated with physical, mental, and social problems which causes serious disorders in marital relationships. Therefore, the present study aimed to compare the effectiveness of Transactional analysis (TA) and Pilates exercises on Psychic restlessness and the general health of infertile women. Materials and Methods: The present applied and quasi-experimental study with pre-test, post-test, and control group was conducted on infertile women referred to Kermanshah Obstetrics and Gynecology Hospital, Kermanshah, Iran in 2020-2021. A total of 75 individuals were selected according to the inclusion criteria and randomly divided into experimental and control groups. The research instruments were the Psychic restlessness Questionnaire by Alikhani and Kazemi Haghighi (2017) and the General Health Questionnaire (GHQ-28) by Goldberg  (1972). It was a two-hour session. Results: A significant difference was observed between the experimental and control groups. The findings indicate that training based on Transactional analysis (TA) and Pilates exercises are effective for Psychic restlessness and the general health of infertile women (F= 34.361 and P< 0.05, F= 26.240 and P< 0.05). Also, the comparison of the obtained means suggests that learning based on the Transactional analysis (TA) approach is more effective in mental changes and health of infertile women compared to Pilates exercises. Conclusion: Methods based on interpersonal relationships and emotional issues can be concluded to reduce the level of Psychic restlessness and improve the mental health of infertile women which is an important treatment for infertility in couples.